A graph-based approach for sustainable walking tour recommendations: The case of Lisbon overcrowding - Peixoto, Ana Rita Henrique (2019)
Motivation: Mass tourism brought problems of carrying capacity in city management. More and more tourists flock to the most famous zones, thereby causing overcrowding situations, while other sustainable points of interest (POIs) are under-visited. Goal: Allow local tourism managing authorities to assemble a database of georeferenced sustainable POIs. Then, combine the latter with local crowding data and implement a walking tour recommender system. Proposal: A web platform to experts adds, in an intuitive way by using a map,POIs with sustainable data. Creating a new database of Lisbon (case of study) sustainable POIs. Implement a tour generator graph-algorithm that receives: user preferences, tour constraints, sustainable POIs and crowd data. Providing a customize tour, that obeys the domain constraints, suggests sustainable POIs and avoids the more crowded areas. Solving a multicriteria shortest path problem. Conclusion: Evidence is provided on the feasibility of computing walking tour recommendations, meeting multiple and complex constraints, namely by promoting sustainability and mitigating crowding, using a graph search algorithm.